2013
DOI: 10.1155/2013/248050
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal Diagnosis of 4p and 4q Subtelomeric Microdeletion in De Novo Ring Chromosome 4

Abstract: Ring chromosomes are unusual abnormalities that are observed in prenatal diagnosis. A 23-year-old patient (gravida 1, para 0) referred for amniocentesis due to abnormal maternal serum screening result in the 16th week of second pregnancy. Cytogenetic analysis of cultured amniyotic fluid cells revealed out ring chromosome 4. Both maternal and paternal karyotypes were normal. Terminal deletion was observed in both 4p and 4q arms of ring chromosome 4 by fluorescence in situ hybridization (FISH). However deletion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…On the other hand, fetal growth restriction was observed in the fetal period (in the studies cases), so it cannot be ruled out that intellectual disability may occur during in childhood and after birth. In addition, another similar study conducted by Akbas et al [ 20 ] demonstrated a case of 2.449Mb terminal 4q35.2 microdeletion in a fetus with growth retardation, also associated with 4p16.3 deletion (size 130 kb without covering the Wolf Hirschhorn critical region). Another related study [ 21 ] elicited a 5.75 Mb interstitial deletion in the 4q35.1q35.2 region in the mother and her two daughters who had no remarkable phenotypic defects.…”
Section: Discussionmentioning
confidence: 84%
“…On the other hand, fetal growth restriction was observed in the fetal period (in the studies cases), so it cannot be ruled out that intellectual disability may occur during in childhood and after birth. In addition, another similar study conducted by Akbas et al [ 20 ] demonstrated a case of 2.449Mb terminal 4q35.2 microdeletion in a fetus with growth retardation, also associated with 4p16.3 deletion (size 130 kb without covering the Wolf Hirschhorn critical region). Another related study [ 21 ] elicited a 5.75 Mb interstitial deletion in the 4q35.1q35.2 region in the mother and her two daughters who had no remarkable phenotypic defects.…”
Section: Discussionmentioning
confidence: 84%
“…Previously, an interstitial deletion of 5.75 Mb has been described in the genomic region 4q35.1-q35.2 between 184,717, 878 and 190,469,337 bp without discernible clinical effects [60]. In other cases, proportional to the size of the loss in 4q35, four genes were in the deletion of 2, 449,000 bp [48], and 19 genes were in the deletion of 5, 090,342 bp [40].…”
Section: Discussionmentioning
confidence: 99%
“…In our case and six other cases with ring chromosome 4 [3,40,42,44,48,51], array-CGH was used to delimit the loss. However, only in our case and the other four cases [3,42,44,48] has the loss been identified in 4p with an average size of 975,315 bp (range, 130,153-1,710,458 bp), and in this and two other cases [40,48], the loss in 4q has an average size of 3,531, 973 bp (range, 2,449,000-5,090,342 bp) (Fig. 6).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation